الكفاءة الاجتماعية وعلاقتها بالعنف في الوسط المدرسي - مداسي, يمينة السعدية; بلعسلة, فتيحة (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى التعرف على علاقة الكفاءة الاجتماعية بالعنف في الوسط المدرسي لدى المراهقين المتمدرسين ببعض متوسطات ولاية الوادي. تتلخص مشكلة الدراسة في فحص العلاقة الإرتباطية بين الأداء على مقياسي الكفاءة الاجتماعية والعنف في الوسط المدرسي لدى أفراد عينة من المراهقين المتمدرسين بمتوسطة الشهيد بن ناصر بوبكر - تغزوت، ومتوسطة الشهيد باهي عبد الرزاق بالرقيبة حسب متغير الجنس. وقد تكونت العينة الكلية لهذه الدراسة من 85 مراهق ومراهقة متمدرسين بإحدى المتوسطات المذكورة سابقا. ومن بين النتائج التي توصلت إليها الدراسة الحالية: 1-لا توجد علاقة ارتباطية ذات دلالة احصائية بين درجات الكفاءة الاجتماعية وبين درجات العنف المدرسي لدى أفراد عينة الدراسة 2-لا توجد فروق ذات دلالة احصائية بين درجات الذكور والإناث على مقياس الكفاءة الاجتماعية ومقياس العنف في الوسط المدرسي لدى أفراد عينة الدراسة . Abstract: This study aimed to identify the relationship of social competence with violence in the school environment among school-age adolescents in some of some school in the state of Elo oued. The problem of the study is summarized in examining the correlation , between ,performance on the measures of social competence and violence in the school environment among members of a sample o f adolescents schooled in the martyr bin Nasser Boubaker - Taghzout school, and the school of the martyr Bahi Abd Al-Razzaq Balraqiba, according to the gender variable. The total sample for this study consisted of 85 male and female adolescents schooled with one of the above mentioned averages. : Among the findings of the current study 1-There is no statistically significant correlational relationship between degrees of social competence and degrees of school violence among the individuals of the study sample 2 -There are no statistically significant differences between the scores of males and females on the scale of social competence and the measure of violence in the school environment among the members of the study sample.
لدى المراهقين المتمدرسي
مقال
Keywords: الكفاءة الاجتماعية، العنف المدرسي، المراهق المتمدرس; social competence, school violence, schools